Effects of Inhaled Nitric Oxide Administration on Early Postoperative Mortality in Patients Operated for Correction of Atrioventricular Canal Defects - Journois, Didier; Baufreton, Christophe; Mauriat, Philippe; Pouard, Philippe; Vouheí, Pascal; Safran, Denis (Chest, 2005)
Objective: Postoperative pulmonary hypertension (POPH) substantially increases mortality after repair of congenital heart diseases. Inhaled nitric oxide (NO) has been reported as an effective and specific means of controlling POPH crisis. No randomized, placebo-controlled study has addressed the ability of NO administration to reduce mortality. Such a trial could raise ethical questions. Design: Observational study with historical control subjects based on multivariate confounder scores. Setting: Surgical pediatric ICU in a university hospital. Patients: Two hundred ninety-four records of patients operated on for atrioventricular (AV) canal between 1984 and 1994 who presented with severe POPH. Interventions: All variables found to be predictive for death by univariate tests were entered in a multivariate forward stepwise logistic regression model. Two paired groups regarding risk factors for death and only differing for POPH treatment (NO or conventional treatment) were constructed on the basis of predicted values obtained from this model. Twenty-five patients received NO, and 39 control patients, operated on between 1984 and 1994, received conventional treatment for POPH. Measurements and results: Postoperative pulmonary pressure, date of operation, and occurrence of an infectious complication were retained in the model. The comparison between the two paired groups showed a significant difference in mortality (24%; 95% confidence interval [CI], 7 to 41%; vs 56%; 95% CI, 37 to 75%, respectively; p = 0.02). Conclusions: This study suggests that there is a high probability for postoperative mortality reduction associated with administration of inhaled NO when severe POPH occurs in children operated for complete repair of AV canal.